2001
DOI: 10.1046/j.1523-1755.2001.0590041315.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin stimulates type I collagen production in db/db mesangial cells: Glucose uptake and TGF-β type II receptor expression

Abstract: Leptin increases glucose uptake and type I collagen in db/db mesangial cells through a PI-3K-dependent pathway. We postulate that increased leptin levels may transmit a signal through the short-form leptin receptor to up-regulate TbetaRII and activate the intraglomerular TGF-beta system, which may contribute to the glomerulosclerosis of obesity or type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 41 publications
(6 reference statements)
8
86
0
2
Order By: Relevance
“…The db/db mouse, which lacks signalling through the leptin receptor, is an excellent model of type 2 diabetes because it develops hyperphagia, obesity, hyperleptinaemia and overt hyperglycaemia [40]. In this study, db/db mice, with or without resveratrol treatment, ate about twice the amount eaten by the db/m mice.…”
Section: Discussionmentioning
confidence: 82%
“…The db/db mouse, which lacks signalling through the leptin receptor, is an excellent model of type 2 diabetes because it develops hyperphagia, obesity, hyperleptinaemia and overt hyperglycaemia [40]. In this study, db/db mice, with or without resveratrol treatment, ate about twice the amount eaten by the db/m mice.…”
Section: Discussionmentioning
confidence: 82%
“…Leptin is a potential progression promoter 45 and enhances the effect of TGF-b. 46,47 The action of leptin in some cells is mediated by norepinephrine, a leptin-inducible neurotransmitter. Against this background, it is of interest that both ACE-i and D3-RA reduced leptin concentrations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that leptin may act directly as a renal growth and fibrogenic factor, stimulating proliferation of glomerular endothelial cells and collagen production in mesangial cells. 13,21 The fact that the latter effect occurred in db/db mouse mesangial cells, which lack the functional long form of the leptin receptor (ob.R L ), and that abundant short leptin receptor isoform (ob.R s ) is detected in abundance in kidney tissue 22 suggests that the direct effects of leptin on the kidney are mediated via ob.R s . Leptin has also been shown to directly increase diuresis and natriuresis without altering blood pressure or potassium excretion.…”
Section: Discussionmentioning
confidence: 99%